2011
DOI: 10.3810/pgm.2011.07.2307
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in Insulin-Treated Diabetes: A Case for Increased Vigilance

Abstract: Studies have shown that effective diabetes management can delay or prevent the micro- and macrovascular complications of diabetes. Achieving optimal glycemic control often requires treatment with intensive insulin management. However, with intensive insulin management comes the risk of severe hypoglycemia. Hypoglycemia requiring emergency medical assistance is as common in patients with longstanding insulin-treated type 2 diabetes mellitus as in patients with type 1 diabetes mellitus, and is associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 93 publications
0
36
0
Order By: Relevance
“…This is important given the negative impact of a fear of hypoglycemia on glycemic control, which has been observed in insulin-treated patients. 25 Physicians reported that most of the therapy adjustments were prompted the IMS reports, and that use of the reports reduced the time required to make therapeutic decisions and enhanced communications with patients, suggesting that use of an IMS tool can provide additional support to analyze, interpret and communicate complex SMBG data and patterns, supported by the indication that 4 out of 5 physicians would use an IMS in the future. These findings are similar to those seen in the STeP study, 3 which, in addition to significant HbA1c reductions, showed that use of structured SMBG via a paper data collection form (AccuChek 360º View tool, Roche Diagnostics, Indianapolis, IN, USA) resulted in more therapy changes, improved quality and efficiencies in patient-physician discussions in noninsulin-treated diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This is important given the negative impact of a fear of hypoglycemia on glycemic control, which has been observed in insulin-treated patients. 25 Physicians reported that most of the therapy adjustments were prompted the IMS reports, and that use of the reports reduced the time required to make therapeutic decisions and enhanced communications with patients, suggesting that use of an IMS tool can provide additional support to analyze, interpret and communicate complex SMBG data and patterns, supported by the indication that 4 out of 5 physicians would use an IMS in the future. These findings are similar to those seen in the STeP study, 3 which, in addition to significant HbA1c reductions, showed that use of structured SMBG via a paper data collection form (AccuChek 360º View tool, Roche Diagnostics, Indianapolis, IN, USA) resulted in more therapy changes, improved quality and efficiencies in patient-physician discussions in noninsulin-treated diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose levels < 50 mg/dl can interfere with patients' ability to perform everyday tasks, resulting in cognitive deterioration, irritability, belligerent behavior, fatigue, visual failure, dysarthria, disorientation, coma, and seizures. 9 Hypoglycemia-induced dementia has been observed in elderly patients, although the mechanism by which cognitive impairment occurs is not clear. 10 Recurrent hypoglycemia lowers or even eliminates the blood glucose concentration threshold at which patients develop a sympathetic response likely to prompt them to take evasive action in time to reverse an impending event.…”
Section: Neurological Impairment After a Hypoglycemic Eventmentioning
confidence: 99%
“…9 The devices consist of three components: a disposable sensor that measures the current or signal generated by the presence of glucose, a transmitter that is attached to the sensor and powers the electrical chemical glucose reaction in the device, and a receiver that displays and stores glucose information. Using an applicator or insertion device, patients insert a sensor wire under their skin.…”
Section: Using Cgm Devicesmentioning
confidence: 99%
“…Severe hypoglycemia can be reduced through vigilance in identifying patients at risk, utilization of appropriate therapy, and effective use of glucose monitoring technologies. 7 The mySentry system represents the first device that relays a complete set of insulin pump and CGM data to a remote monitoring station. As such, it can provide parents with a complete picture of pump status and glycemic trends for children sleeping in a different room in the house.…”
Section: Discussionmentioning
confidence: 99%